Bone health of the Ovahimba people of north-western Namibia in the context of urbanization and a change of the sociocultural environment. (3rd April 2017) - Wilhelm, Anneke; Hadji, Peyman; Münzel, Mark; Daniel, Hanna; Flache, Stephan; Nyarango, Peter; Kann, Peter Herbert
Abstract: The prevalence of osteoporosis in Sub-Saharan African (SSA) countries is low, however, as urbanization takes root, it is predicted that bone health will decrease dramatically. The bone health of the semi-nomadic Ovahimba people of Namibia was investigated in the context of urbanization and changes of the sociocultural environment. Furthermore, data on bone health in SSA countries is scarce; there exists no ethnic-specific reference group for people of black origin. Included in the study were 98 urban and rural living Ovahimba people. Quantitative ultrasound was performed, sunrise/sunset saliva cortisol concentrations was measured and a questionnaire was conducted. There was no significant difference in the QUS parameters, however, after adjustment for confounders, SOS and SI differed significantly. The saliva cortisol concentrations differed significantly. After adjustment for confounders, saliva cortisol was significantly negatively correlated to SOS (r= −0.27, p  = 0.021) giving an indication for an association between cortisol concentration and QUS parameters. The urban group furthermore showed a nutritional transition. Even though the bone health of the Ovahimba is very good, first signs of the adverse effects of urbanization were detected. Beside changes of lifestyle, this may be attributed to an increased cortisol exposure of the Ovahimba people living in an urban environment due to an increased psychosocial stress.